NSC348884 cytotoxicity is not mediated by inhibition of nucleophosmin oligomerization - Šašinková, Markéta; Heřman, Petr; Holoubek, Aleš; Strachotová, Dita; Otevřelová, Petra; Grebeňová, Dana; Kuželová, Kateřina; Brodská, Barbora (Scientific reports, 2021)
Nucleophosmin (NPM) mutations causing its export from the nucleoli to the cytoplasm are frequent in acute myeloid leukemia (AML). Due to heterooligomerization of wild type NPM with the AML-related mutant, the wild-type becomes misplaced from the nucleoli and its functions are significantly altered. Dissociation of NPM heterooligomers may thus restore the proper localization and function of wild-type NPM. NSC348884 is supposed to act as a potent inhibitor of NPM oligomerization. The effect of NSC348884 on the NPM oligomerization was thoroughly examined by fluorescence lifetime imaging with utilization of FRET and by a set of immunoprecipitation and electrophoretic methods. Leukemia-derived cell lines and primary AML cells as well as cells transfected with fluorescently labeled NPM forms were investigated. Our results clearly demonstrate that NSC348884 does not inhibit formation of NPM oligomers neither in vivo nor in vitro. Instead, we document that NSC348884 cytotoxicity is rather associated with modified cell adhesion signaling. The cytotoxic mechanism of NSC348884 has therefore to be reconsidered.
Keywords: Nuclear Proteins; jaderné proteiny; nádorové buněčné linie; indoly; Nucleophosmin; Indoles; Leukemia; protinádorové látky; apoptóza; HEK293 buňky; Humans; Cell Line, Tumor; leukemie; Antineoplastic Agents; HEK293 Cells; lidé; Apoptosis; nukleofosmin